Revealing martensitic transformation and α/β interface evolution in electron beam melting three-dimensional-printed Ti-6Al-4V - Tan, Xipeng (2018)
As an important metal three-dimensional printing technology, electron beam melting (EBM) is gaining increasing attention due to its huge potential applications in aerospace and biomedical fields. EBM processing of Ti-6Al-4V as well as its microstructure and mechanical properties were extensively investigated. However, it is still lack of quantitative studies regarding its microstructural evolution, indicative of EBM thermal process. Here, we report α′ martensitic transformation and α/β interface evolution in varied printing thicknesses of EBM-printed Ti-6Al-4V block samples by means of atom probe tomography. Quantitative chemical composition analysis suggests a general phase transformation sequence. By increasing in-fill hatched thickness, elemental partitioning ratios arise and β volume fraction is increased. Furthermore, we observe kinetic vanadium segregation and aluminum depletion at interface front and the resultant α/β interface widening phenomenon. It may give rise to an increased α/β lattice mismatch and weakened α/β interfaces, which could account for the degraded strength as printing thickness increases.